# Solve for the variable.Check solution.  -3(y-3y)+4=-4(3y-y)+6+13y

Asked on by kim609

### 3 Answers |Add Yours

jgeertz | College Teacher | (Level 1) Associate Educator

Posted on

`-3(y-3y)+4 =-4(3y-y)+6+13y`

Start by combining like terms inside the parentheses.

`-3(-2y) +4 = -4(2y) +6 +13y`

Multiply terms inside the parentheses by `-3` on the left side of the equation and `-4` on the right side of the equation.

`6y +4 = -8y +6 +13y`

Combine like terms on the right side of the equation.

`6y+4 = 5y +6`

Now subtract `5y` from both sides of the equation.

`1y +4 =6`

Subtract `4` from both sides of the equation.

`1y=2`

`y=2`

Check your solution by plugging your answer into the original equation.

`-3(2-3(2))+4 = -4(3(2)-2) +6 +13(2)`

`-3(-4) +4 = -4(4)+6+26`

`12+4=-16+6+26`

`16= -16+32`

`16=16`  Check

The solution is y=2.

atyourservice | Student, Grade 11 | (Level 3) Valedictorian

Posted on

-3(y-3y)+4=-4(3y-y)+6+13y

-3y+9y+4=-12y+4y+6+13y combine like terms

6y+4=5y+6 now combine like terms again

6y-5y=6-4

1y=2

y=2

harsha2359 | Student, Undergraduate | (Level 1) eNoter

Posted on

-3y +9y +4 = -12y +4y +6 + 13y

i.e y = 2..

We’ve answered 317,286 questions. We can answer yours, too.